Two new species of Microvelia Westwood, 1834 (Hemiptera: Heteroptera: Veliidae) from Colombia, with a key to Colombian species - Padilla-Gil, Dora N.; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2013)
Only six species of Microvelia have been recorded from Colombia up to the present, namely M. ancona, M. hinei, M. leucothea, M. longipes, M. panamensis, and M. pulchella. Microvelia inguapi sp. n. and M. piedrancha sp. n. are herein described and compared with similar species. An identification key to the Colombian species of Microvelia is presented.